Genetic diversity of the threatened Saussurea dorogostaiskii (Asteraceae) in the Khuvsgul region of Mongolia - Nudkhuu Nyamgerel; Shukherdorj Baasanmunkh; Batlai Oyuntsetseg; Dashzeveg Oyuntsetseg; Joscelyn Norris; Hyeok Jae Choi; Gun-aajav Bayarmaa (Sigmul bunryu hag-hoeji = Korean journal of plant taxonomy, 2023)
Saussurea dorogostaiskii Palib. (Asteraceae) is a critically endangered medicinal plant in Mongolia and Russia. We studied the genetic variation of S. dorogostaiskii from three mountains of northern Mongolia. The genetic profile was assessed in 70 individuals from eight populations using five inter-simple sequence repeat markers, producing 53 loci with 96.4% polymorphism across all bands. Shannon’s index (I) and Nei’s gene diversity (H) value at the species level of S. dorogostaiskii are 0.25 and 0.17, respectively. An AMOVA showed high genetic variation among the populations (22% of populations and 32% of mountains), consistent with the high genetic differentiation (GST = 0.49) and low gene flow (Nm = 0.51) in S. dorogostaiskii populations. Eight populations were clustered into two groups, corresponding to their geographic locations. The low within-population genetic diversity and high genetic differentiation among S. dorogostaiskii populations factor into their endangered designation. This genetic analysis reveals that all populations are equally threatened, and community-based conservation is appropriate for these species.